Determinants of Market Leadership in India's Smartphone Industry: A Factor-Analytic and Regression Approach - Shanmugam, Karthick; Arivazhagan , Dr.R. (International Journal of Accounting and Economics Studies, 2025)
This study uses a combined exploratory-confirmatory research methodology to discover the structural determinants of market leadership in India's smartphone industry. Grounded in the Resource-Based View and Consumer Utility Theory, the research proposes a multidimensional framework that validates 22 attributes across 11 smartphone brands through primary survey data (N = 2,500). An Exploratory Factor Analysis (EFA) with Varimax rotation recognized five latent constructs, collectively explaining 84.3% of the variance. Hierarchical regression analysis emphasized Premium Experience (β = 1.78, p < 0.001) and Value Proposition (β = 1.42, p = 0.002) as the key predictors of market share (R² = 0.93). Vivo arose as the market leader, leveraging a hybrid strategy that meritoriously balances premium features (Camera: 3.93) with affordability (Value-for-Money: 3.74). In contrast, gaps in perceived value hindered Apple's novelty leadership. This research finding contributes to the development of the Attribute Bundling Theory in the perspective of emerging markets and provides actionable, empirically supported strategic insights for industry stakeholders.